Effects of Exposed Rock on Soil and Water Loss and Hydrodynamic Characteristics of Karst Slope Land - HE Maolin; LI Rui; WU Panpan; XIONG Ling; XIAO Linlü (Shuitu Baochi Xuebao, 2024)
[Objective] The effects of exposed rocks on the runoff, sediment yield, and hydrodynamic characteristics of slope land needs further study. [Methods] Through the laboratory simulation test, the slope lands with different rock exposure rates (0, 10%, 30%, 50%, 70%) were set, and the artificial simulation rainfall test under different rainfall intensities (30, 60, 90 mm/h) was carried out, in order to explore the impact of rainfall intensity and exposed rocks on runoff, sediment yield and hydrodynamic characteristics of slope land. [Results] The surface runoff and sediment yield of slope land increased with the increased of rainfall intensity, and decreased with the increase of rock exposure rate. Under varying rainfall intensities, the runoff and sediment yield of slopes with 0 and 10% rock exposure rates slope land were not significantly difference in most cases (p>0.05), but the slope with a 0 rock exposure rate was significantly difference from other slopes with rock exposure (p<0.05). There was a significant difference in runoff and sediment yield between lands with low rock exposure rates (10%) and lands with high rock exposure rate (50% or more) (p<0.05). Flow velocity (V), Flow depth (h), Reynolds number (Re), Froude number (Fr), Water flow shear stress (τ) and Flow power (w) increased with the increased of rainfall intensity, the Friction coefficient (f) decreased with the increase of rainfall intensity. The Flow velocity (V), and Froude number (Fr) decreased with the increased of rock exposure rate, while the Flow depth (h) and Friction coefficient (f) increased with the increase of rock exposure rate, and the change regulation of Reynolds number (Re), Water flow shear stress (τ) and Flow power (w) were disparate in different rainfall intensity. Moreover, there were certain differences in hydrodynamic parameters among different slope lands. The quantitative relationship between sediment yield and hydrodynamic parameters was best fitted by Exponential function, Flow velocity (V), (R2=0.819, p<0.05), Water flow shear stress (τ)(R2=0.858, p<0.05) and Flow power (w) (R2=0.890, p<0.05) had better prediction effects on sediment yield of slope land, and Flow power (w) was the best prediction parameter. [Conclusion] The development of this study has further enriched the theory of soil erosion in karst areas, and can provide reference for the establishment of water erosion prediction model suitable for exposed rock slope land.